2004
DOI: 10.1111/j.1600-0501.2004.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical long‐term radiographic evaluation of graft height changes after maxillary sinus floor augmentation with a 2 : 1 autogenous bone/xenograft mixture and simultaneous placement of dental implants

Abstract: The aim of the present study was to assess long-term changes in sinus-graft height after maxillary sinus floor augmentation and simultaneous placement of implants. A total of 191 patients who underwent maxillary sinus floor augmentation were radiographically followed for up to about 10 years. A 2 : 1 mixture of autogenous bone and bovine xenograft (Bio-Oss) was used as the graft material. Sinus-graft height was measured using 294 panoramic images immediately after augmentation and up to 108 months subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
248
4
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(291 citation statements)
references
References 29 publications
26
248
4
4
Order By: Relevance
“…The radiopacity of graft materials is also a valuable tool for evaluating the localization of the graft and its resorption degree in periodic radiographies (4,(51)(52)(53)(54). The radiopacity of a sufficient degree of bone grafts also facilitates the assessment of the success of sinus-lifting procedures.…”
Section: Bone Graft Materialsmentioning
confidence: 99%
“…The radiopacity of graft materials is also a valuable tool for evaluating the localization of the graft and its resorption degree in periodic radiographies (4,(51)(52)(53)(54). The radiopacity of a sufficient degree of bone grafts also facilitates the assessment of the success of sinus-lifting procedures.…”
Section: Bone Graft Materialsmentioning
confidence: 99%
“…The patients provided written informed consent prior to surgery. Ten patients (five males and five females, mean age: 50 y/o), affected with class V or VI maxillary atrophy [4] with less than 3 mm of residual horizontal ridge [15] formed the study group.…”
Section: Methodsmentioning
confidence: 99%
“…Once the sinus has been accessed, the Schneiderian membrane is carefully elevated away from the sinus floor. Bone graft material is then placed between the local host bone and the elevated membrane to enable simultaneous or delayed placement of dental implants [1,4]. The long-term success rate of dental implants increases when bone graft materials are replaced or surrounded by newly formed bone, which grows from the patient's existing bone into the augmented area [5].…”
Section: Introductionmentioning
confidence: 99%
“…Note, how ever, that maxillary sinus bone graft using autogenous bone was found to lead to considerable bone resorption over time. In particular, Hatano et al 4) cited the possibility of pneumatization for the first 2~3 years after bone grafting. In their study using computed tomography (CT), Johansson et al 5) stated that maxillary sinus bone graft using autogenous bone harvested from iliac bone led to the resorption of 49.5% of graft material 6 or 7 months after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Later, many clinical and histolo gical studies on maxillary sinus bone graft material have been reported. In particular, Hatano et al 4) recommended the com bined use of allogenous bone and synthetic bone and autogenous bone. Jensen et al 9) noted that residual alveolar bone height had the most influence on the survival rate of the implant placed after maxillary sinus elevation, and that, if the height was 7 mm or less, bone graft must be done for implant placement.…”
Section: Introductionmentioning
confidence: 99%